The religious correlates of death anxiety: a systematic review and meta-analysis - Jong, Jonathan (Religion, brain & behavior, 2018)
Various theories of religion hypothesize a connection between death anxiety and religiosity. In particular, Terror Management Theory’s worldview defence hypothesis predicts that death anxiety is lowest among very religious and irreligious individuals, and highest among uncertain individuals. Likewise, the supposition that death anxiety motivates religious belief, which in turn mitigates death anxiety, predicts that religiosity increases with death anxiety among non-believers, and that death anxiety decreases as religiosity increases among believers. In both cases, a curvilinear relationship - specifically, an inverted-U curve - is predicted. We extracted 202 effect sizes from 100 studies for an "omnibus" religiosity meta-analysis, and six meta-analyses that examine particular dimensions of religiosity. We found high heterogeneity and a weak negative association between death anxiety and religiosity. A closer examination revealed that 10 of the 11 studies that directly tested for curvilinearity provided some support for an inverted-U pattern. The curvilinearity hypothesis cannot be ruled out, but more evidence - particularly on non-religious individuals, and in non-Western, non-Abrahamic contexts - is needed.